OPTIMALISASI TATA LETAK PABRIK PADA PROSES PENGECATAN DI PT INKA (Persero) MENGGUNAKAN METODE SYSTEMATIC LAYOUT PLANNING (SLP) - Edi Winarno; Putu Dana Karningsih (UNIVERSITAS PGRI MADIUN, 2024)
PT INKA (Persero) has experienced significant product development but faces issues with delivery delays. One of the causes is waste in the transportation process related to the factory layout. Re-layout is needed to improve efficiency. This study uses the Systematic Layout Planning (SLP) method to identify and analyze company data and create the best layout alternatives. The results show that alternative layout 1 with rail is the most suitable for painted passenger/engine cars, unpainted passenger/engine cars, and freight wagons. Alternative layout 1 provides high efficiency in material handling costs and re-layout costs. Optimizing process time and organizing work areas are also crucial to achieving production capacity targets. This is expected to address production delays and improve responsiveness to changes in the production environment.